The Public Information Disclosure in State Madrasah Aliyah - Ahmad Umar; Muhammad Munadi; Aminuddin Aminuddin; Tato Priyo Sulistyono (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This study aimed to determine the implementation model of public information disclosure at MAN 2 Pesisir Selatan in West Sumatra province. This study used content analysis research with the data originating from websites, along with the documents and developments downloaded from the websites related to public information disclosure activities at MAN 2 Pesisir Selatan. This study was conducted from November to December 2022. The data validity used source triangulation by validating data in documents on the websites under study in one feature and across features. The data were analyzed using an interactive analysis model. The results show that the public information disclosure implemented in MAN 2 Pesisir Selatan was through providing a place and the main website connected to the PPID website. The PPID website contained complete profiles and types of report information following existing regulations. There were types of information and reports with institutional dimensions, and institutional actors, so good and clean institutions could reflect excellent and clean executors.